FESTA DO VINHO DA MADEIRA, TURISMO E IDENTIDADE CULTURAL - Marujo, Noémi (2017)
Madeira Wine Festival is a special event that seeks to maintain, through its various cultural manifestations, the cultural identity of Madeira associated to the vineyard and wine. Through the feast the host community tries to resist global culture brought about by the globalization process. In fact, the festivals that reflect the cultural identity of a region operate as an excellent 'gun' to valorize the cultural traditions. On the other hand, also help to promote a destination or to improve the tourism image of a region. This Communication aims to show how the Madeira Wine Festival is a valued element of cultural identity related to the wine.